Electrochemical device and electronic device
Patent Information
- Application Number
- CN202380066860.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2025-04-22
AI Technical Summary
Existing lithium-ion batteries have safety risks in high-temperature and high-humidity environments, including gas production, excessive expansion, and combustion caused by internal gas accumulation. Moreover, existing additives have poor suppression effects at high temperatures, and increased packaging tension will cause heat accumulation to fail. release.
By using a combination of tab glue and electrolyte in an electrochemical device, the thickness of the tab glue is 0.025≤t≤0.14mm, and the electrolyte contains non-fluorinated cyclic carbonate, fluorinated cyclic carbonate, carboxylate and Linear carbonate, and adjust its content relationship to meet a specific ratio relationship to reduce gas production and improve sealing, and increase the use of nitrile compounds and lithium salts to improve SEI membrane stability.
Significantly reduces the gas production and excessive expansion of electrochemical devices at high temperatures, improves sealing and storage safety, reduces the generation of hydrofluoric acid caused by moisture intrusion, enhances the oxidation resistance of the electrolyte, and improves the overall Storage security.
Smart Images

Figure CN119866561A_ABST
Abstract
Description
Electrochemical devices and electronic devices Technical Field
[0001] The present application relates to the field of energy storage, and in particular to an electrochemical device, especially a lithium-ion battery. Background Art
[0002] Secondary batteries (particularly lithium-ion batteries), as convenient electrochemical devices, have been widely used in electronic products such as laptops in recent years. Due to the characteristics of their application areas, people have increasingly stringent requirements for the safety of electronic products, which places higher demands on the storage performance of electrochemical devices in high-temperature and high-humidity environments.
[0003] Currently, in commercial lithium-ion batteries, lithium salts (e.g., LiPF6) are typically dissolved in a variety of carbonate solvents, such as cyclic carbonates (e.g., ethylene carbonate (EC), propylene carbonate (PC), etc.) and linear carbonates (e.g., diethyl carbonate (DEC), dimethyl carbonate (DMC), etc.), as electrolytes to form a solid electrolyte interface (SEI) film on the surface of the active material. The SEI film can effectively reduce side reactions of the electrolyte on the surface of the active material and improve the safety performance of the lithium-ion battery.
[0004] In addition, commercial lithium-ion batteries are prone to generating gas after being fully charged and stored, which can cause the lithium-ion battery to swell and lead to safety hazards. Usually, the storage safety of lithium-ion batteries can be improved by adding positive electrode additives to the electrolyte or increasing the tension of the battery package. Although the addition of positive electrode additives can inhibit the oxidative decomposition reaction of carbonate solvents on the positive electrode side, thereby reducing the gas production of lithium-ion batteries, in high temperature and high humidity environments, the positive electrode additives have poor inhibitory effect on the oxidative decomposition reaction of carbonate solvents. Although increasing the tension of the battery package can block the infiltration of moisture from the outside of the battery package in a high humidity environment, the gas production of the electrolyte containing carbonate solvents at high temperatures will increase, causing heat accumulation inside the electrode assembly and preventing the internal gas from being released. In severe cases, it can also lead to violent combustion.
[0005] In view of this, it is indeed necessary to continue to research and improve electrochemical devices in order to provide an electrochemical device with improved storage safety in a high temperature and high humidity environment.
[0006] Summary of the Invention
[0007] The present application provides an electrochemical device and an electronic device to at least some extent solve at least one problem existing in the related art.
[0008] According to one aspect of the present application, some embodiments of the present application provide an electrochemical device comprising a tab and an electrolyte, wherein the tab comprises a tab metal strip, which includes, in sequence along its length, a head hollow foil region, a tab glue-covered region, and a tail connection region, wherein the tab glue-covered region is provided with tab glue, and the tab glue has a thickness of t mm; and the electrolyte comprises at least a non-fluorinated cyclic carbonate, a fluorinated cyclic carbonate, a carboxylic acid ester, and a linear carbonate. The tab glue thickness t (mm) ranges from 0.025 ≤ t ≤ 0.14. By controlling the interaction between the tab glue thickness and the electrolyte composition, the gas generation phenomenon of the electrochemical device at high temperature can be significantly reduced, and the sealing effect of the tab glue sealing area can be ensured, thereby improving the storage safety of the electrochemical device.
[0009] In some embodiments, based on the mass of the electrolyte, the content of non-fluorinated cyclic carbonate is A%, the content of fluorinated cyclic carbonate is B%, the content of carboxylate is C%, and the content of linear carbonate is D%. The electrochemical device satisfies at least one of the following relationships:
[0010] (1) 0.005×(C / D+5)≤t;
[0011] (2) 0.1 ≤ C / D ≤ 8; or
[0012] (3)4≤A / B≤20.
[0013] Research has found that limiting the content of non-fluorinated cyclic carbonates and fluorinated cyclic carbonates, the content of carboxylates and linear carbonates, or adjusting the relationship between the thickness of the tab glue and the content of the electrolyte components significantly reduces the gas production of the electrochemical device at high temperatures, significantly improves the transitional expansion of the electrochemical device at high temperatures, and significantly reduces the phenomenon of the electrochemical device reacting with lithium salts due to water intrusion to produce hydrofluoric acid (HF), thereby significantly improving the storage safety of the electrochemical device.
[0014] In some embodiments, the content A% of the non-fluorinated cyclic carbonate in the electrolyte is in the range of 10≤A≤40. In some embodiments, the content A% of the non-fluorinated cyclic carbonate in the electrolyte is in the range of 20≤A≤40.
[0015] In some embodiments, the content B% of the fluorinated cyclic carbonate in the electrolyte is in the range of 1≤B≤10. In some embodiments, the content B% of the fluorinated cyclic carbonate in the electrolyte is in the range of 1.5≤B≤7.
[0016] In some embodiments, the range of the content C% of the carboxylic acid ester in the electrolyte is: 5≤C≤60. In some embodiments, the range of the content C% of the carboxylic acid ester in the electrolyte is: 20≤C≤50.
[0017] In some embodiments, the content D% of the linear carbonate in the electrolyte is in the range of 7≤D≤60. In some embodiments, the content D% of the linear carbonate in the electrolyte is in the range of 15≤D≤45.
[0018] In some embodiments, the electrolyte satisfies the following relationship: 0.2≤C / D≤4.
[0019] In some embodiments, the electrolyte satisfies the following relationship: 4≤A / B≤15.
[0020] When the content of non-fluorinated cyclic carbonates, fluorinated cyclic carbonates, carboxylates and / or linear carbonates in the electrolyte meets the above conditions, it helps to optimize the solid electrolyte interface (SEI) film formed by the electrolyte on the electrode active material layer during the cycle, reduce the gas generation phenomenon of the electrolyte at high temperature, or improve the cycle kinetics of the electrolyte, thereby helping to further improve the storage safety of the electrochemical device in a high temperature and high humidity environment.
[0021] In some embodiments, 0.03≤t≤0.10. When the thickness of the tab glue is within the above range, the infiltration of the electrolyte into the tab glue can be further reduced, the sealing of the tab glue sealing area can be improved, and the storage safety of the electrochemical device in a high temperature and high humidity environment can be further improved.
[0022] In some embodiments, the tab adhesive has a bonding strength of f N / mm to the tab adhesive-covered area, where 3 ≤ f ≤ 55. The bonding strength of the tab adhesive to the tab adhesive-covered area affects the package tension of the electrochemical device package. When the bonding strength of the tab adhesive to the tab adhesive-covered area is within the above range, excellent package bonding strength is provided, preventing external moisture from penetrating the battery and preventing corrosion of the internal electrolyte in high-humidity environments, thereby further improving the storage safety of the electrochemical device in high-temperature and high-humidity environments.
[0023] In some embodiments, the water content of the electrolyte is r ppm, where 200≤r≤2000. Controlling the water content in the electrolyte can reduce the reaction between the lithium salt and water vapor at high temperature to form hydrofluoric acid.
[0024] In some embodiments, the non-fluorinated cyclic carbonate comprises one or more of ethylene carbonate, propylene carbonate, vinylene carbonate, or vinylethylene carbonate.
[0025] In some embodiments, the fluorinated cyclic carbonate comprises one or more of fluoroethylene carbonate or bisfluoroethylene carbonate.
[0026] In some embodiments, the linear carbonate comprises one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl trifluoroethyl carbonate, trifluoromethyl ethylene carbonate, or bis(2,2,2-trifluoroethyl) carbonate.
[0027] In some embodiments, the carboxylic acid ester comprises a compound represented by Formula I below,
[0028] in:
[0029] R 11 Selected from hydrogen, hydroxy, substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 1-12 Alkoxy, substituted or unsubstituted C 2-12 Alkenyl, substituted or unsubstituted C 6-12 Aryl or substituted or unsubstituted C 6-26 aryloxy;
[0030] R 12 is selected from hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-12 Alkenyl or substituted or unsubstituted C 6-26 aryl;
[0031] When substituted, the substituent is halogen.
[0032] In some embodiments, the carboxylic acid ester comprises one or more of propyl propionate (PP), ethyl propionate (EP), ethyl acetate (EA), ethyl formate, methyl acetate, propyl acetate, butyl butyrate, ethyl difluoroacetate, difluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl propionate, or methyl trifluoropropionate.
[0033] In some embodiments, the electrolyte further comprises a nitrile compound, wherein the content of the nitrile compound is 0.1% to 12% by mass of the electrolyte, and the nitrile compound comprises one or more compounds represented by Formula II to Formula V.
[0034] in:
[0035] R 21 Selected from substituted or unsubstituted C 1-12 Alkylene or substituted or unsubstituted C 1-12 Alkyleneoxy;
[0036] R 31 and R 32 are each independently selected from a single bond or substituted or unsubstituted C 1-12 alkylene;
[0037] R 41 、R 42 and R 43 are each independently selected from a single bond, a substituted or unsubstituted C 1-12 Alkylene or substituted or unsubstituted C1-12 Alkyleneoxy;
[0038] R 51 Selected from substituted or unsubstituted C 1-12 Alkylene, substituted or unsubstituted C 2-12 Alkenylene, substituted or unsubstituted C 6-26 Arylene or substituted or unsubstituted C 2-12 Heterocyclic group;
[0039] When substituted, the substituent is halogen.
[0040] In some embodiments, the nitrile compound includes one or more of the following compounds: malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sebacononitrile, 3,3'-oxydipropionitrile, hexane-2-enedinitrile, fumaronitrile, 2-pentanedinonitrile, methylglutaronitrile, 4-cyanopimelonitrile, (Z)-but-2-enedinitrile, 2,2,3,3-tetrafluorosuccinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,5-pentanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyano)propane, 1,1,3,3-propanetetracarbonitrile,
[0041] In some embodiments, the content of the nitrile compound is 1% to 8% by weight of the electrolyte.
[0042] The cyano group in nitrile compounds has strong coordination properties and can complex with high-valent metal ions (such as nickel, cobalt, manganese, etc.) on the electrode surface, masking the ionic activity, inhibiting the decomposition and gas production of the electrolyte on the electrode surface, and enhancing the oxidation resistance of the electrolyte, which helps to further improve the storage safety of electrochemical devices in high temperature and high humidity environments.
[0043] In some embodiments, the electrolyte further comprises a lithium salt, wherein the lithium salt comprises one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3 (LiFSI), LiN(SO2CF3)2 (LiTFSI), LiC(SO2CF3)3, LiSiF6, LiBOB, or LiDFOB.
[0044] In some embodiments, the content of the lithium salt is 5% to 20% by mass of the electrolyte. By controlling the content of the lithium salt, the storage performance of the electrochemical device in a high temperature and high humidity environment can be optimized.
[0045] According to another aspect of the present application, some embodiments of the present application provide an electronic device, which includes the electrochemical device of the above embodiment.
[0046] The present application can significantly optimize the storage safety of electrochemical devices in high temperature and high humidity environments by controlling the content relationship of non-fluorinated cyclic carbonates, fluorinated cyclic carbonates, carboxylates and linear carbonates in the electrolyte and adjusting the thickness of the tab glue.
[0047] Additional aspects and advantages of the present application will be described, shown, or explained in part in the following description through implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The following briefly describes the drawings necessary to describe the embodiments of the present application or the prior art to facilitate the description of the embodiments of the present application. Obviously, the drawings described below only represent some of the embodiments of the present application. Those skilled in the art can, without requiring creative effort, derive drawings for other embodiments based on the structures illustrated in these drawings.
[0049] FIG1 is a schematic diagram of the side view and top view of a tab according to some embodiments of the present application.
[0050] FIG2 is a schematic diagram of the side view and top view of the sealing portion according to some embodiments of the present application. DETAILED DESCRIPTION
[0051] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0052] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "one or more of," "one or more of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "one or more of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "one or more of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0053] Furthermore, for ease of description, “first,” “second,” “third,” etc. may be used herein to distinguish different components in a figure or a series of figures. Unless otherwise specified or limited, “first,” “second,” “third,” etc. are not intended to describe corresponding components.
[0054] In addition, amounts, ratios, and other numerical values are sometimes presented herein in a range format. It should be understood that such a range format is used for convenience and brevity and should be interpreted flexibly to include not only the values explicitly specified as limits of the range, but also all individual values or sub-ranges encompassed within the range, as if each value and sub-range were explicitly specified.
[0055] Unless expressly stated otherwise, the following terms used herein have the meanings indicated below.
[0056] The term "C x " refers to a carbon atom with x number of carbon atoms. For example, C1- 10 The alkyl group is an alkyl group having 1 to 10 carbon atoms.
[0057] The term "alkyl" is intended to be a straight chain saturated hydrocarbon structure having 1 to 20 carbon atoms. "Alkyl" is also intended to be a branched or cyclic hydrocarbon structure having 3 to 20 carbon atoms. For example, an alkyl group can be C1 to C 20 Alkyl, C1 to C 10 Alkyl, C1 to C5 alkyl, C5 to C 20 Alkyl, C5 to C 15 Alkyl or C5 to C 10 Alkyl. When an alkyl group having a specific number of carbon atoms is specified, all geometric isomers having that number of carbon atoms are contemplated; thus, for example, "butyl" is meant to include n-butyl, sec-butyl, isobutyl, tert-butyl, and cyclobutyl; "propyl" includes n-propyl, isopropyl, and cyclopropyl. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, ethylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, n-heptyl, octyl, cyclopropyl, cyclobutyl, norbornyl, and the like. Additionally, alkyl groups may be optionally substituted.
[0058] The term "alkenyl" refers to a monovalent unsaturated hydrocarbon group which may be straight or branched and has at least one, and typically 1, 2 or 3, carbon-carbon double bonds. Unless otherwise defined, an alkenyl group typically contains 2 to 20 carbon atoms, e.g., may be C2 to C 20 Alkenyl, C6 to C 20 Alkenyl, C2 to C 12 Alkenyl or C2 to C6 alkenyl. Representative alkenyl groups include, for example, vinyl, n-propenyl, isopropenyl, n-but-2-enyl, but-3-enyl, n-hex-3-enyl, etc. In addition, the alkenyl group can be optionally substituted.
[0059] The term "alkynyl" refers to a monovalent unsaturated hydrocarbon group which may be straight or branched and has at least one, and typically one, two or three, carbon-carbon triple bonds. Unless otherwise defined, an alkynyl group typically contains from 2 to 20 carbon atoms, e.g., may be C2 to C 20 Alkynyl, C6 to C 20 Alkynyl, C2 to C 10 Alkynyl or C2 to C6 alkynyl. Representative alkynyl groups include, for example, ethynyl, prop-2-ynyl (n-propynyl), n-but-2-ynyl, n-hex-3-ynyl, etc. In addition, the alkynyl group can be optionally substituted.
[0060] The term "alkoxy" refers to an alkyl group attached to the parent structure through an oxygen atom (-O-alkyl). Examples include, but are not limited to, methoxy, ethoxy, propoxy, isopropoxy, cyclopropyloxy, butoxy, sec-butoxy, tert-butoxy, pentyloxy, cyclohexyloxy, and the like.
[0061] The term "aryl" encompasses monocyclic and polycyclic ring systems. Polycyclic rings may have two or more rings in which two carbon atoms are common to two adjacent rings (the rings are "fused"), wherein at least one of the rings is aromatic, e.g., the other rings may be cycloalkyl, cycloalkenyl, aryl, heterocycle, and / or heteroaryl. For example, an aryl group may be C6 to C 50 Aryl, C6 to C 40 Aryl, C6 to C 30 Aryl, C6 to C 20 Aryl or C6 to C 10 Aryl. Representative aryl groups include, for example, phenyl, methylphenyl, propylphenyl, isopropylphenyl, benzyl, and naphth-1-yl, naphth-2-yl, and the like. Additionally, aryl groups may be optionally substituted.
[0062] The term "aryloxy" refers to an alkaryl group (-O-aryl) attached to the parent structure through an oxygen atom. Examples include, but are not limited to, phenoxy, benzyloxy, 4-methylphenoxy, 3-methylphenoxy, 2-methylphenoxy, 4-ethylphenoxy, 3-ethylphenoxy, 2-ethylphenoxy, 4-n-propylphenoxy, 3-n-propylphenoxy, 2-n-propylphenoxy, 4-isopropylphenoxy, 3-isopropylphenoxy, 2-isopropylphenoxy, 4-n-butylphenoxy, 3-n-butylphenoxy, 2-n-butylphenoxy, 4-isobutylphenoxy, 3-isobutylphenoxy, 2-isobutylphenoxy, 4-tert-butylphenoxy, 3-tert-butylphenoxy, 2-tert-butylphenoxy, 3,5-dimethylphenoxy, 2,6-dimethylphenoxy, 3,5-diethylphenoxy, 2,6-diethylphenoxy, 3,5-di-n-propylphenoxy, 2,6-n-propylmethylphenoxy, 3,5-diisopropylphenoxy, 2,6-diisopropylphenoxy, 3,5-di-n-butylphenoxy, 2,6-di-n-butylphenoxy, 4-methylbenzyloxy, 3-methylbenzyloxy, 2-methylbenzyloxy, 4-ethylbenzyloxy, 3-ethylbenzyloxy, 2-ethylbenzyloxy, 3,5-diisopropylbenzyloxy, 2,6-diisopropylbenzyloxy, 1-naphthyloxy, 2-naphthyloxy and the like.
[0063] The term "heterocyclic group" encompasses aromatic and non-aromatic cyclic groups. Heteroaromatic cyclic groups also refer to aromatic heterocyclic groups. In some embodiments, heteroaromatic cyclic groups and heteronon-aromatic cyclic groups are C1 to C2 containing at least one heteroatom. 50 Heterocyclic group, C1 to C 40 Heterocyclic group, C1 to C 30 Heterocyclic group, C1 to C 20 Heterocyclic group, C1 to C 10 Heterocyclic group, C1 to C6 heterocyclic group. Representative heterocyclic groups include, for example, morpholinyl, piperidinyl, pyrrolidinyl, and the like, and cyclic ethers such as tetrahydrofuran, tetrahydropyran, and the like. In addition, the heterocyclic group may be optionally substituted.
[0064] As used herein, the term "halogen" may be F, Cl, Br, or I.
[0065] In the field of electrochemical energy storage, as electrochemical devices are used in more and more fields, the application environments faced by electrochemical devices are becoming more and more diverse. This has led to the need for continuous research and optimization of the safety performance of electrochemical devices in order to maintain cycle performance and storage performance in extreme environments.
[0066] Under high temperature and high humidity operating conditions, electrochemical devices need to consider many aspects of the problem. For example, most electrochemical devices (such as lithium-ion batteries) use a mixture of carbonate solvents, lithium salts and some additives as the electrolyte. Among them, carbonate solvents have good SEI film formation and repair capabilities and are common solvents for maintaining normal charging and discharging of commercial lithium-ion battery systems. Under normal circumstances, the formation of the SEI film can effectively reduce the side reactions caused by direct contact between the electrolyte and the positive / negative active materials, such as gas production, lithium precipitation, etc. However, under high temperature conditions, carbonate solvents are easily oxidized and decomposed on the positive electrode side to produce gas.
[0067] Electrochemical devices require a certain level of packaging strength to isolate the external environment from the internal electrode assembly and reduce moisture penetration and battery failure in high-humidity environments. However, excessive packaging strength can lead to heat accumulation within the electrode assembly, preventing internal gas from being released and, in severe cases, causing violent combustion.
[0068] Through mechanism research, it is found that the electrolyte protection additives, solvent and water content, and cell packaging reliability have different effects on the failure mode of electrochemical devices under high temperature and high humidity operating conditions.
[0069] In view of the above-mentioned problems, the present application provides an electrochemical device comprising a tab and an electrolyte, wherein: the tab comprises a tab metal strip, which, along its length, includes a head hollow foil region, a tab glue-covered region, and a tail connection region; the tab glue-covered region is provided with tab glue, and the tab glue has a thickness of t mm, where 0.025 ≤ t ≤ 0.14; and the electrolyte comprises a non-fluorinated cyclic carbonate, a fluorinated cyclic carbonate, a carboxylic acid ester, and a linear carbonate. By controlling the interaction between the tab glue thickness and the electrolyte composition, gas generation in the electrochemical device at high temperatures can be significantly reduced, while ensuring the sealing effect of the tab glue sealing area, reducing electrolyte erosion, and improving the storage safety of the electrochemical device, particularly in high-temperature and high-humidity environments.
[0070] Based on the mass of the electrolyte, the content of non-fluorinated cyclic carbonate is A%, the content of fluorinated cyclic carbonate is B%, the content of carboxylate is C%, and the content of linear carbonate is D%. The electrochemical device satisfies at least one of the following relationships: (1) 0.005×(C / D+5)≤t; (2) 0.1≤C / D≤8; or (3) 4≤A / B≤20. By adjusting the content of carboxylate and linear carbonate in the electrolyte, the carboxylate can replace part of the carbonate, thereby improving the gas generation of the electrolyte and reducing the corrosion of the electrolyte on the tab glue. In addition, the reaction of cyclic carbonate at the positive electrode at high temperature is one of the main factors causing the gas generation of the electrolyte. Therefore, the present application significantly reduces the gas production phenomenon of the electrochemical device at high temperature by limiting the content of non-fluorinated cyclic carbonates and fluorinated cyclic carbonates, the content of carboxylates and linear carbonates, or adjusting the relationship between the thickness of the ear glue and the content of the electrolyte components, significantly improves the combustion phenomenon of the electrochemical device at high temperature due to transitional expansion, and significantly reduces the phenomenon of the electrochemical device reacting with lithium salts due to moisture intrusion to produce hydrofluoric acid (HF), thereby significantly improving the storage safety of the electrochemical device.
[0071] In some embodiments, the ratio of the carboxylate content to the linear carbonate content is 0.2 ≤ C / D ≤ 4. In some embodiments, the ratio of the carboxylate content to the linear carbonate content is 0.5 ≤ C / D ≤ 3. In some embodiments, the ratio of the carboxylate content to the linear carbonate content is 1 ≤ C / D ≤ 2. In some embodiments, the ratio of the carboxylate content to the linear carbonate content, C / D, is 0.1, 0.2, 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, or a value within a numerical range formed by any two of the foregoing values. When the ratio of the carboxylate content to the linear carbonate content is within the foregoing range, it helps to further improve the storage safety of the electrochemical device in a high temperature and high humidity environment.
[0072] In some embodiments, the content relationship between non-fluorinated cyclic carbonate and fluorinated cyclic carbonate is 4≤A / B≤20. In some embodiments, the content relationship between non-fluorinated cyclic carbonate and fluorinated cyclic carbonate is 4≤A / B≤15. In some embodiments, the content relationship between non-fluorinated cyclic carbonate and fluorinated cyclic carbonate is 5≤A / B≤15. In some embodiments, the content relationship A / B between non-fluorinated cyclic carbonate and fluorinated cyclic carbonate is: 4, 5, 7, 9, 11, 14.5, 17, 18, 20 or a value within the numerical range formed by any two of the above values. When the content relationship between non-fluorinated cyclic carbonate and fluorinated cyclic carbonate is within the above range, it helps to further improve the storage safety of the electrochemical device in a high temperature and high humidity environment.
[0073] In some embodiments, 10≤A≤40. In some embodiments, 20≤A≤40. In some embodiments, the content A% of the non-fluorinated cyclic carbonate is 10%, 15%, 20%, 25%, 30%, 35%, 40%, or a value within a numerical range formed by any two of the foregoing values.
[0074] In some embodiments, 1 ≤ B ≤ 10. In some embodiments, 1.5 ≤ B ≤ 7. In some embodiments, 1.5 ≤ B ≤ 5. In some embodiments, the content B% of the fluorinated cyclic carbonate is 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a value within a numerical range formed by any two of the above values.
[0075] In some embodiments, 5 ≤ C ≤ 60. In some embodiments, 10 ≤ C ≤ 55. In some embodiments, 20 ≤ C ≤ 50. In some embodiments, 30 ≤ C ≤ 40. In some embodiments, the carboxylate content (C%) is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or a value within a range formed by any two of the foregoing values.
[0076] In some embodiments, 7 ≤ D ≤ 60. In some embodiments, 10 ≤ D ≤ 50. In some embodiments, 15 ≤ D ≤ 45. In some embodiments, 20 ≤ D ≤ 30. In some embodiments, the linear carbonate content (D%) is 7%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or a value within a range formed by any two of the foregoing values.
[0077] When the content of non-fluorinated cyclic carbonates, fluorinated cyclic carbonates, carboxylates and / or linear carbonates in the electrolyte is within the above range, it helps to optimize the solid electrolyte interface (SEI) film formed by the electrolyte on the electrode active material layer during the cycle, reduce the gas production of the electrolyte at high temperature, or improve the cycle kinetics of the electrolyte, thereby helping to further improve the storage safety of the electrochemical device in a high temperature and high humidity environment.
[0078] Without departing from the spirit of the present application, the types of non-fluorinated cyclic carbonates, fluorinated cyclic carbonates, carboxylates and / or linear carbonates may be any suitable carbonates and / or carboxylates in the art.
[0079] In some embodiments, the non-fluorinated cyclic carbonate comprises at least one or more of ethylene carbonate, propylene carbonate, vinylene carbonate, or vinylethylene carbonate.
[0080] In some embodiments, the fluorinated cyclic carbonate comprises one or more of fluoroethylene carbonate or bisfluoroethylene carbonate.
[0081] In some embodiments, the linear carbonate comprises one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl trifluoroethyl carbonate, trifluoromethyl ethylene carbonate, or bis(2,2,2-trifluoroethyl) carbonate.
[0082] In some embodiments, the carboxylic acid ester comprises a compound represented by Formula I below,
[0083] in:
[0084] R 11 Selected from hydrogen, hydroxy, substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 1-12 Alkoxy, substituted or unsubstituted C 2-12 Alkenyl, substituted or unsubstituted C 6-12 Aryl or substituted or unsubstituted C 6-26 aryloxy;
[0085] R 12 is selected from hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-12 Alkenyl or substituted or unsubstituted C 6-26 aryl;
[0086] When substituted, the substituent is halogen.
[0087] In some embodiments, the carboxylate comprises one or more of propyl propionate, ethyl propionate, ethyl acetate, ethyl formate, methyl acetate, propyl acetate, butyl butyrate, ethyl difluoroacetate, difluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl propionate, or methyl trifluoropropionate.
[0088] According to other embodiments of the present application, the water content in the electrolyte is controlled by a vacuum drying process before the electrolyte is injected, which can further reduce the hydrofluoric acid (HF) generated by the reaction between water and lithium salts. In some embodiments, the water content of the electrolyte is r (ppm), wherein 200≤r≤2000. In some embodiments, wherein 500≤r≤1000. In some embodiments, the water content r (ppm) of the electrolyte is 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000 or a value within a numerical range formed by any two of the above values.
[0089] In some embodiments, the electrolyte further includes an additive. Without departing from the spirit of the present application, the additive may be any suitable additive in the art.
[0090] In some embodiments, the electrolyte further comprises a nitrile compound to improve the stability of the SEI film, wherein the nitrile compound comprises one or more compounds represented by the following formula II to formula V:
[0091] in:
[0092] R 21 Selected from substituted or unsubstituted C1-12 alkylene or substituted or unsubstituted C1-12 alkyleneoxy;
[0093] R 31 and R 32 Each is independently selected from a single bond or a substituted or unsubstituted C1-12 alkylene group;
[0094] R 41 、R 42 and R 43 Each is independently selected from a single bond, a substituted or unsubstituted C1-12 alkylene group or a substituted or unsubstituted C1-12 alkyleneoxy group;
[0095] R 51 is selected from a substituted or unsubstituted C1-12 alkylene group, a substituted or unsubstituted C2-12 alkenylene group, a substituted or unsubstituted C6-26 arylene group, or a substituted or unsubstituted C2-12 heterocyclic group;
[0096] When substituted, the substituent is halogen.
[0097] In some embodiments, the nitrile compound comprises one or more of the following compounds: malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, octanedinitrile, sebacononitrile, 3,3'-oxydipropionitrile, hexane-2-enedinitrile, fumaronitrile, 2-pentene dinitrile, methylglutaronitrile, 4-cyanopimelonitrile, (Z)-but-2-enedinitrile, 2,2,3,3-tetrafluorosuccinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,5-pentanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoxy)propane, 1,1,3,3-propanetetracarbonitrile,
[0098] In some embodiments, the content of the nitrile compound is 0.5% to 10% by weight of the electrolyte. In some embodiments, the content of the nitrile compound is 1% to 8% by weight of the electrolyte. In some embodiments, the content of the nitrile compound is 3% to 8% by weight of the electrolyte. In some embodiments, the content of the nitrile compound is 3% to 6% by weight of the electrolyte. In some embodiments, the content of the nitrile compound is 0.1%, 0.2%, 0.5%, 1.0%, 2.0%, 5.0%, 8.0%, 10%, 12%, or a value within a range formed by any two of the foregoing values.
[0099] The cyano group in nitrile compounds has strong coordination properties and can complex with high-valent metal ions (such as nickel, cobalt, manganese, etc.) on the electrode surface, masking the ionic activity, inhibiting the decomposition and gas production of the electrolyte on the electrode surface, and enhancing the oxidation resistance of the electrolyte, thereby improving the high-temperature and high-voltage safety performance of the battery.
[0100] In some embodiments, the electrolyte further comprises a lithium salt, wherein the lithium salt comprises one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3 (LiFSI), LiN(SO2CF3)2 (LiTFSI), LiC(SO2CF3)3, LiSiF6, LiBOB, and LiDFOB.
[0101] In some embodiments, the lithium salt content is 5% to 20% by weight of the electrolyte. In some embodiments, the lithium salt content is 5%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or a value within a range formed by any two of the foregoing values. By controlling the lithium salt content, the storage performance of the electrochemical device in high temperature and high humidity environments can be optimized.
[0102] The tab is an electrode terminal that electrically connects to the electrode assembly and extends through the battery package to the outside. As shown in Figure 1, the tab comprises a tab metal strip 10, which is arranged along its length in sequence to include a head hollow foil region 101, a tab glue-covered region 102, and a tail connection region 103. Tab glue-covered region 102 is provided with tab glue 20. The head hollow foil region 101 is used to connect to any suitable external connector, and the tail connection region 103 is used to electrically connect to the electrode assembly of the electrochemical device.
[0103] The tab glue covers the tab glue coverage area, and the tab glue is bonded to the battery package to form a sealing portion with the battery package. In some embodiments, the outermost layer of the tab glue further comprises a molten resin layer, and the tab glue and the battery package are melted to form a sealing portion. In a high temperature and high humidity environment, the thickness of the tab glue is easily affected by the environmental humidity or the interaction of the electrolyte components, which affects the packaging structure of the electrochemical device. The tab glue thickness test can be performed by any suitable method / device in the art. In some embodiments, the specific implementation method of the tab glue thickness test is as follows: the sealing portion of the electrochemical device is placed in the manner of the side view schematic diagram of Figure 1 or Figure 2, and the thickness of the double-layer tab glue of the sealing portion is measured by a high-precision CCD measuring instrument (with an accuracy higher than 5 microns) to be 2t (mm), and the thickness of the single-layer tab glue is calculated to be t (mm).
[0104] In some embodiments, 0.025≤t≤0.14. In some embodiments, 0.03≤t≤0.10. In some embodiments, 0.05≤t≤0.10. In some embodiments, the thickness t (mm) of the tab glue is: 0.025, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, or a value within a numerical range formed by any two of the above values. When the tab glue thickness is within the above range, it can reduce the infiltration and erosion of the electrolyte on the tab glue, which helps to further improve the storage safety of the electrochemical device in a high temperature and high humidity environment.
[0105] Due to the electrochemical device manufacturing process, the tab adhesive's bond to the tab metal strip is a highly susceptible area within the battery's seal. When the electrochemical device deforms or expands due to stress, this bond preferentially peels. Therefore, the adhesive strength of the tab adhesive to the tab adhesive-covered area is equivalent to the electrochemical device's packaging tensile force. In some embodiments, this adhesion of the tab adhesive to the tab metal strip can affect the isolation between the electrolyte and the external environment, thereby impacting the overall packaging strength of the electrochemical device and its structural safety during cycling.
[0106] In some embodiments, the adhesion of the tab glue to the tab glue covering area is f N / mm, where 3≤f≤55. In some embodiments, 5≤f≤50. In some embodiments, 10≤f≤40. In some embodiments, 20≤f≤30. In some embodiments, f is 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, or a value within a numerical range formed by any two of the above values. When the adhesion of the tab glue to the tab glue covering area is within the above range, excellent packaging bonding strength can be provided, preventing external moisture from penetrating into the battery in a high humidity environment and preventing corrosion of the internal electrolyte, thereby further improving the storage safety of the electrochemical device in a high temperature and high humidity environment.
[0107] The battery packaging can be any suitable packaging in the art. In some embodiments, the battery packaging is an aluminum-plastic film. In some embodiments, the tab structure of the present application is referenced from a tab structure of a secondary battery disclosed in Chinese patent application CN106784998A. The secondary battery can effectively provide packaging strength to its electrode assembly by combining the tab glue of the composite tab with the outer packaging film to form a seal. The entire text of Chinese patent application CN106784998A is incorporated herein by reference to provide a specific illustrative embodiment of the tab and seal structure of the electrochemical device of the present application.
[0108] As shown in Figure 2, in some embodiments, the battery package further includes an outer packaging laminate mold 30, and the outer packaging laminate film 30 can correspond to the setting position of the pole ear 10 and the pole ear glue 20 of the electrochemical device, and overlap with the pole ear glue covering area 102 to form a sealing portion. The outer packaging laminate film 30 includes an outer resin layer 301, a metal layer 302, and an inner resin layer 303 stacked in sequence. In some embodiments, a first adhesive layer (not shown in the drawings) is further included between the outer resin layer 301 and the metal layer 302, and a second adhesive layer (not shown in the drawings) is further included between the metal layer 302 and the inner resin layer 303. In some embodiments, the outer packaging laminate film 30 may further have a matte layer (not shown in the drawings) outside the outer resin layer.
[0109] In some embodiments, the electrochemical device is a lithium-ion battery. The lithium-ion battery also includes an electrode assembly. Without departing from the spirit of the present application, the electrode assembly structure in the electrochemical device of the present application can be any suitable electrode assembly in the art, without limitation. In some embodiments, the electrode assembly is a wound structure or a multi-pole lug structure. In some embodiments, the electrode assembly can be a laminate structure or a multi-pole lug structure. In some embodiments, the electrode assembly includes a positive electrode, a negative electrode, and a separator, wherein the separator is disposed between the positive electrode plate and the negative electrode plate.
[0110] The positive electrode includes a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector can be aluminum foil or nickel foil, however, other positive electrode current collectors commonly used in the art can be used without limitation. In some embodiments, the positive electrode active material layer includes a positive electrode active material capable of absorbing and releasing lithium (Li) (hereinafter sometimes referred to as "positive electrode active material capable of absorbing / releasing lithium Li"). Without violating the spirit of the present application, the specific type of positive electrode active material is not subject to specific restrictions and can be selected as needed. Examples of positive electrode active materials capable of absorbing / releasing lithium (Li) may include lithium cobaltate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium iron phosphate, lithium titanate and lithium-rich manganese-based materials. One or more.
[0111] In some embodiments, the positive electrode active material layer can further include a binder. It will be understood by those skilled in the art that, without departing from the spirit of the present application, the binder can be any suitable binder material in the art. In some instances, the binder includes, but is not limited to, one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0112] In some embodiments, the positive electrode active material layer can further include a conductive agent. It should be understood by those skilled in the art that, without violating the spirit of the present application, the conductive agent can be any suitable conductive agent material in the art. In some instances, the conductive agent includes, but is not limited to, one or more carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber), metal materials (e.g., metal powder, metal fiber, etc., including, for example, one or more of elemental copper, elemental aluminum, elemental silver), and conductive polymers (e.g., polyphenylene derivatives).
[0113] The negative electrode includes a current collector and a negative electrode active material layer provided on the current collector. The current collector of the negative electrode can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, however, other negative electrode current collectors commonly used in the art can be used without limitation. In some embodiments, the negative electrode active material layer comprises a negative electrode active material capable of absorbing and releasing lithium (Li) (hereinafter sometimes referred to as "negative electrode active material capable of absorbing / releasing lithium Li"). Without violating the spirit of the present application, the specific type of negative electrode active material is not subject to specific restrictions and can be selected according to demand. Examples of negative electrode active materials capable of absorbing / releasing lithium Li include natural graphite, artificial graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , one or more of Li-Al alloys.
[0114] In some embodiments, the negative electrode active material layer may include a binder and, optionally, a conductive agent. Without departing from the spirit of the present application, the binder and / or conductive agent may be any suitable binder material and / or conductive agent material in the art. Examples of the binder and / or conductive agent are similar to those listed for the positive electrode active material layer and will not be described in detail herein.
[0115] A separator between the positive and negative electrodes can prevent short circuits. The material and shape of the separator used in the embodiments of this application are not particularly limited and can be any known prior art. In some embodiments, the separator comprises a polymer or inorganic material that is stable to the electrolyte of this application. In some embodiments, the separator comprises, but is not limited to, at least one selected from polyethylene, polypropylene, polyethylene terephthalate, polyimide, and aramid.
[0116] It should be understood that the preparation method of the electrochemical device in the embodiment of the present application, and the preparation method of each component of the electrochemical device including: tabs, electrolyte, battery package, positive electrode, negative electrode and diaphragm, without violating the spirit of the present application, can be any suitable preparation method in the art, and is not limited by the embodiment of the present application. In one embodiment of the method for manufacturing an electrochemical device, the preparation method of a lithium-ion battery comprises: winding, folding or stacking the negative electrode, diaphragm and positive electrode in the embodiment into an electrode assembly in sequence, then loading the electrode assembly into a battery package, and injecting the electrolyte, and then subjecting the lithium-ion battery loaded with the electrode assembly to subsequent vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery. In some embodiments, the method for manufacturing an electrochemical device further comprises a vacuum drying step before injecting the electrolyte, loading the electrode assembly into the battery package, and baking and drying the battery to which no electrolyte is added.
[0117] Some embodiments of the present application further provide an electronic device, which includes the electrochemical device in the embodiments of the present application.
[0118] The electronic devices of the embodiments of the present application are not particularly limited. In some embodiments, the electronic devices may include, but are not limited to, laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors.
[0119] Specific embodiments
[0120] Some specific embodiments and comparative examples are listed below and their electrochemical devices (lithium-ion batteries) are tested respectively to better illustrate the technical solution of the present application.
[0121] I. Test Method
[0122] 1.1 Quality test of each component in the electrolyte
[0123] Discharge the lithium-ion battery at a constant current of 0.1C to 2.8V. Weigh the battery and calculate its mass as m. Then disassemble the battery and quickly extract the resulting bare electrode assembly and outer foil / plastic film in high-purity acetonitrile (≥99.9%). Gas chromatography is performed on the resulting supernatant to determine the relative content p of each component in the electrolyte. Dry the extracted bare cell and outer foil / plastic film in a vacuum oven. Weigh the total mass of the dried bare cell and outer foil / plastic film and calculate it as m'.
[0124] The mass of the electrolyte n = mm', and the mass of each component in the electrolyte is the product of the mass n of the electrolyte and the relative content p of each component. For example: the mass of propionate (PP) = n x p (relative content of propionate).
[0125] 1.2 Electrolyte water content test
[0126] According to the test method for the mass of each component in the electrolyte in 1.1 above, the extraction method is used to extract the clear liquid from a certain amount of high-purity acetonitrile, and the water content r is tested by the Karl Fischer method. The test temperature is 15°C to 28°C, and the ambient humidity is <1%. The water content r test result is the percentage of the electrolyte calculated after excluding the acetonitrile mass.
[0127] 1.3 Package tensile strength test (adhesion of tab glue to tab metal strip)
[0128] The lithium-ion battery was discharged at a constant current of 0.1C to 2.8V and disassembled. The sealing part at the tab of the disassembled battery was cut into a sample with a width of 6mm. The sample was clamped on a high-speed rail tensile testing machine. The ambient temperature was set and heated to a predetermined temperature of 85°C. The temperature was kept for 5 minutes. The package tensile force f (N / mm) during peeling was tested at 180° and a tensile speed of 175±5mm / min.
[0129] 1.4 Storage safety test under high temperature and high humidity environment
[0130] A lithium-ion battery was discharged at 0.2C to 3.0V at room temperature (25°C), and then charged at 1C to 4.48V. This was recorded as the initial state. The thickness η of the lithium-ion battery in the initial state was measured using a micrometer. The lithium-ion battery was then placed in an environment with 85°C and 40% humidity for 18 hours, and the thickness η' of the lithium-ion battery was measured using a micrometer. The thickness change rate of the lithium-ion battery was calculated using the following formula: (η' / η-1) × 100%.
[0131] II. Preparation Method
[0132] 2.1 Preparation of positive electrode
[0133] The cathode active material, lithium cobalt oxide (LiCoO2), conductive carbon black (Super P), and polyvinylidene fluoride (PVDF), are mixed in a weight ratio of 97:1:2. N-methylpyrrolidone (NMP) is added as a solvent and stirred evenly in a vacuum mixer to obtain a cathode slurry. The cathode slurry is evenly coated on the cathode current collector aluminum foil and dried at 90°C. The cathode is then cold pressed, cut, and slit to obtain the cathode.
[0134] 2.2 Preparation of negative electrode
[0135] The negative electrode active material artificial graphite, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a weight ratio of 97:1:2, deionized water is added, and a negative electrode slurry is obtained under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the copper foil is dried, then cold pressed, cut into pieces, slit, and dried under vacuum conditions to obtain a negative electrode sheet.
[0136] 2.3 Preparation of electrolyte
[0137] In an environment with a water content of less than 150 ppm (in a dry argon atmosphere), carbonate solvents and carboxylate solvents were mixed according to the ratios listed in Table 1, additives were added according to the settings of the examples or comparative examples, and after dissolving and thoroughly stirring, lithium salt was added and mixed to obtain an electrolyte. It should be noted that:
[0138] Comparative Example 1-1 uses a conventional solvent EC:PC:DEC = 1:2:7. The relative proportions of the various components of the solvent in the comparative examples and / or examples are prepared as shown in Table 1; in Examples 2-1 to 2-9 and Examples 3-1 to 3-13, the ratio of carbonate solvents to carboxylic acid ester solvents is consistent with that in Example 1-4; in Example 2-10, the ratio of carbonate solvents to carboxylic acid ester solvents is consistent with that in Example 1-16.
[0139] In the comparative examples and / or examples shown in Tables 1 and 2, no nitrile was added, and the type and content of the lithium salt used were consistent with those in Examples 1 to 4. In order to illustrate the comparative effects of the content and type of nitrile compounds and lithium salts, relevant experiments were conducted as shown in Table 3.
[0140] The abbreviations of the components in the electrolytes in the following examples and comparative examples and their corresponding compound names are as follows:
[0141] 2.4 Diaphragm
[0142] The separator is a 12 μm thick polyethylene (PE) porous polymer film.
[0143] 2.5 Preparation of lithium-ion batteries
[0144] The positive electrode sheet, separator, and negative electrode sheet are stacked in order using a winding method, with the separator placed between the positive and negative electrodes to act as an insulator. After the wound electrode assembly is dehydrated at high temperature, the tail connection area of the tabs is connected to obtain a dry electrode assembly. The dry electrode assembly is placed in an aluminum-plastic mold, injected with the prepared electrolyte, and then vacuum packaged, allowed to stand, formed, shaped, and tested for capacity to obtain a soft-pack lithium-ion battery. Special instructions are required:
[0145] In the comparative examples and embodiments listed in Table 1, the tab glue provided on the tabs has different thicknesses while maintaining the same packaging parameter conditions; in the embodiments listed in Table 2, different packaging tensions can be obtained by adjusting the packaging pressure and time acting on the heat sealing portion.
[0146] The tabs utilize the secondary battery tab structure disclosed in Chinese patent application CN106784998A. This secondary battery utilizes a composite tab adhesive bonded to the outer packaging film to form a seal, effectively providing packaging strength for the electrode assembly. Tab adhesive thickness can be adjusted by controlling the mold or polymer dosage during the raw material molding process.
[0147] In the comparative examples and examples listed in Table 1, the water content in the electrochemical devices was controlled using standardized material preparation environmental conditions, process parameters, and bare cell processing and packaging requirements. Specifically, the dry electrode assemblies in the comparative examples and examples in Table 1 were baked and dried at 80°C for 5 hours before liquid injection, and at a packaging pressure of 0.45 MPa for 3 seconds.
[0148] In the examples listed in Table 2, the drying temperature and time of the dry electrode assembly before liquid injection were adjusted to achieve different moisture contents, as follows: Example 2-1 used a pre-injection drying condition of 80°C for 5 hours; Examples 2-2 and 2-3 used a pre-injection drying condition of 80°C for 7 hours; Examples 2-4 and 2-9 used a pre-injection drying condition of 90°C for 5 hours; Examples 2-5, 2-6, and 2-10 used a pre-injection drying condition of 90°C for 7 hours; Example 2-7 used a pre-injection drying condition of 90°C for 8 hours; and Example 2-8 used a pre-injection drying condition of 90°C for 9 hours. In the examples listed in Table 2, different packaging tensions can be achieved by adjusting the pressure and time applied to the heat seal. Example 2-2 adopts a packaging pressure of 0.45 MPa and a time of 3 s; Example 2-1 and Example 2-3 adopt a packaging pressure of 0.6 MPa and a time of 3 s; Example 2-4 and Example 2-5 adopt a packaging pressure of 0.45 MPa and a time of 3 s; Example 2-6 and Example 2-8 adopt a packaging pressure of 0.3 MPa and a time of 3 s; Example 2-7 adopts a packaging pressure of 0.28 MPa and a time of 3 s; Example 2-9 adopts a packaging pressure of 0.9 MPa and a time of 5 s; Example 2-10 adopts a packaging pressure of 0.4 MPa and a time of 3 s.
[0149] As can be seen from the test results in Table 1, Comparative Example 1-1 shows that, without the use of carboxylic acid esters and fluorinated cyclic carbonates, the electrolyte containing linear carbonates and non-fluorinated cyclic carbonates is prone to expansion in a high-temperature, high-humidity environment. Although fluorinated cyclic carbonates were further added to the electrolyte in Comparative Example 1-2, the optimization of the SEI film was unable to effectively compensate for the degree of gassing of the carbonate solvent in the electrolyte, resulting in a large degree of expansion of the lithium-ion battery in a high-temperature, high-humidity environment. As shown in Comparative Example 1-3, when the thickness of the tab glue is too small, that is, less than 0.025mm, its sealing performance is poor. After the electrolyte infiltrates the tab glue, it will cause leakage, reducing the storage safety of the lithium-ion battery.
[0150] Compared with the comparative example, as shown in Examples 1-1 to 1-24, when the thickness of the ear glue in the lithium-ion battery is 0.025 mm to 0.14 mm and the electrolyte contains non-fluorinated cyclic carbonates, fluorinated cyclic carbonates, carboxylates and linear carbonates, the gas production of the lithium-ion battery can be effectively reduced, and the storage thickness change rate of the lithium-ion battery in a high temperature and high humidity environment can be reduced, thereby improving its storage safety.
[0151] Furthermore, when the thickness t (mm) of the ear glue and the content A% of non-fluorinated cyclic carbonate, the content B% of fluorinated cyclic carbonate, the content C% of carboxylate and the content D% of linear carbonate in the electrolyte meet at least one of the following conditions: 0.005×(C / D+5)≤t≤0.14, 0.1≤C / D≤8 or 4≤A / B≤20, the storage thickness change rate of the lithium-ion battery in a high temperature and high humidity environment can be further reduced, thereby improving its storage safety.
[0152] In addition, when the lithium-ion battery meets at least one of the following conditions: 10≤A≤40; 20≤A≤40; 1≤B≤10; 1.5≤B≤7; 5≤C≤60; 20≤C≤50; 7≤D≤60; 15≤D≤45; 0.2≤C / D≤4; 0.025≤t≤0.10, the storage thickness change rate of the lithium-ion battery in a high temperature and high humidity environment can be further reduced, thereby improving its storage safety.
[0153] Table 2 lists the relationship between electrolyte water content and package tension for some examples of this application, as well as the results of storage safety tests under high temperature and high humidity environments. Except for the parameters listed in Table 2, Examples 2-1 to 2-9 have the same settings as Example 1-4, and Example 2-10 has the same settings as Example 1-16.
[0154] Table 2
[0155] The results show that when the lithium-ion battery meets at least one of the following conditions: 200≤r≤2000 and 3≤f≤55, the storage safety of the electrochemical device under high temperature and high humidity environment can be further improved.
[0156] Table 3 lists the additives, lithium salt types, and storage safety test results under high temperature and high humidity environments for some examples of this application. Except for the parameters listed in Table 3, the settings of Examples 3-1 to 3-13 are the same as those of Example 1-4.
[0157] Table 3
[0158] Note: N / A means no corresponding value.
[0159] The results show that adding 0.1% to 12% of nitrile compounds to the electrolyte can further improve the storage safety of electrochemical devices under high temperature and high humidity environments.
[0160] In addition, controlling the lithium salt content in the electrolyte within the range of 5% to 20% can further improve the storage safety of the electrochemical device under high temperature and high humidity environments.
[0161] References throughout the specification to "embodiment," "part of an embodiment," "one embodiment," "another example," "an example," "a specific example," or "a part of an example" mean that at least one embodiment or example in the present application includes the particular features, structures, materials, or characteristics described in the embodiment or example. Therefore, descriptions such as "in some embodiments," "in an embodiment," "in one embodiment," "in another example," "in an example," "in a specific example," or "an example" appearing in various places throughout the specification are not necessarily references to the same embodiment or example in the present application. In addition, the particular features, structures, materials, or characteristics herein may be combined in any suitable manner in one or more embodiments or examples.
[0162] Although illustrative embodiments have been shown and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions, and modifications may be made to the embodiments without departing from the spirit, principles, and scope of the present application.
Claims
1. An electrochemical device comprising a tab and an electrolyte, wherein: The tab comprises a tab metal strip, and the tab metal strip comprises a head empty foil area, a tab glue covering area and a tail connection area along the length direction, and the tab glue is arranged on the tab glue covering area, and the thickness of the tab glue is t mm, 0.025≤t≤0.14; The electrolyte contains non-fluorinated cyclic carbonate, fluorinated cyclic carbonate, carboxylic acid ester and linear carbonate.
2. The electrochemical device according to claim 1, wherein the content of the non-fluorinated cyclic carbonate is A%, the content of the fluorinated cyclic carbonate is B%, the content of the carboxylate is C%, and the content of the linear carbonate is D% based on the mass of the electrolyte; and The electrochemical device satisfies at least one of the following relations: (1) 0.005×(C / D+5)≤t; (2) 0.1 ≤ C / D ≤ 8; or (3)4≤A / B≤20.
3. The electrochemical device according to claim 2, wherein the electrolyte satisfies at least one of the following relationships: (1)10≤A≤40; (2)1≤B≤10; (3) 5 ≤ C ≤ 60; or (4)7≤D≤60。 4. The electrochemical device according to claim 2, wherein the electrochemical device satisfies at least one of the following relationships: (a) 0.2≤C / D≤4; (b) 0.03 ≤ t ≤ 0.10; or (c)4≤A / B≤15. 5 . The electrochemical device according to claim 1 , wherein the adhesion force of the tab glue to the tab glue covered area is f N / mm, wherein 3≤f≤55. The electrochemical device according to claim 1 , wherein the water content of the electrolyte is r ppm, wherein 200≤r≤2000.
7. The electrochemical device of claim 1, wherein the non-fluorinated cyclic carbonate comprises one or more of ethylene carbonate, propylene carbonate, vinylene carbonate, or vinylethylene carbonate, the fluorinated cyclic carbonate comprises one or more of fluoroethylene carbonate or bisfluoroethylene carbonate, and the linear carbonate comprises one or more of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl trifluoroethyl carbonate, trifluoromethylethylene carbonate, or bis(2,2,2-trifluoroethyl) carbonate.
8. The electrochemical device according to claim 1, wherein the carboxylic acid ester comprises a compound represented by Formula I, in: R 11 is selected from hydrogen, hydroxy, substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 1-12 Alkoxy, substituted or unsubstituted C 2-12 Alkenyl, substituted or unsubstituted C 6-12 Aryl or substituted or unsubstituted C 6-26 aryloxy; R 12 is selected from hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-12 Alkenyl or substituted or unsubstituted C 6-26 Aryl; When substituted, the substituent is halogen.
9. The electrochemical device of claim 8, wherein the carboxylic acid ester comprises one or more of propyl propionate, ethyl propionate, ethyl acetate, ethyl formate, methyl acetate, propyl acetate, butyl butyrate, ethyl difluoroacetate, difluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl propionate, or methyl trifluoropropionate.
10. The electrochemical device according to claim 1, wherein the electrolyte further comprises a nitrile compound, the content of the nitrile compound is 0.1% to 12% based on the mass of the electrolyte, and the nitrile compound comprises one or more compounds represented by Formula II to Formula V, in: R 21 is selected from substituted or unsubstituted C 1-12 Alkylene or substituted or unsubstituted C 1-12 Alkyleneoxy; R 31 and R 32 are each independently selected from a single bond or a substituted or unsubstituted C 1-12 Alkylene; R 41 , R 42 and R 43 are each independently selected from a single bond, a substituted or unsubstituted C 1-12 Alkylene or substituted or unsubstituted C 1-12 Alkyleneoxy; R 51 is selected from substituted or unsubstituted C 1-12 Alkylene, substituted or unsubstituted C 2-12 Alkenylene, substituted or unsubstituted C 6-26 Arylene or substituted or unsubstituted C 2-12 Heterocyclic group; When substituted, the substituent is halogen.
11. The electrochemical device according to claim 10, wherein the nitrile compound comprises one or more of the following compounds: malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sebacononitrile, 3,3'-oxydipropionitrile, hexane-2-enedinitrile, fumaronitrile, 2-pentene dinitrile, methyl glutaronitrile, 4-cyanopeltanonitrile, (Z)-but-2-enedinitrile, 2,2,3,3-tetrafluorosuccinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,5-pentanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyano)propane, 1,1,3,3-propanetetracarbonitrile, The content of the nitrile compound is 1% to 8% based on the mass of the electrolyte.
12. The electrochemical device according to claim 1, wherein the electrolyte further comprises a lithium salt, the lithium salt comprising one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3(LiFSI), LiN(SO2CF3)2(LiTFSI), LiC(SO2CF3)3, LiSiF6, LiBOB or LiDFOB, wherein the content of the lithium salt is 5% to 20% based on the mass of the electrolyte.
13. The electrochemical device according to claim 1, wherein the electrolyte satisfies at least one of the following relationships: (5)20≤A≤40; (6)1.5≤B≤7; (7) 20 ≤ C ≤ 50; or (8)15≤D≤45。 14. An electronic device comprising the electrochemical device according to any one of claims 1 to 13.